Blueberry production opportunities in Georgia - Chavleishvili, Marina (Ivane Javakhishvili Tbilisi State University Press, 2021)
There is a growing trend in demand for berry crops, including blueberries, worldwide. The European Union, Russia, China, the United Arab Emirates and other countries stand out in this regard. Today, the blueberries produced in the world do not meet the market demand. Exports of raw blueberries to the EU have doubled in the last ten years. However, in the wake of the growing market, the resources available in many regions are not yet fully utilized. It was found out that Georgia has one of the best soil-climatic conditions for the production of blueberries, which allows obtaining quality raw materials in accordance with international standards. Thus, the current situation makes the analysis of blueberry production and its future development even more relevant. It is important to assess the potential of the country in this field in order to determine the parameters of production efficiency, increase the export potential and raise awareness. The paper presents the opportunities for blueberry production in Georgia, market analysis and its development trends. There is assessed the world market of blueberries, the current situation in the article. The export potential of blueberries is analyzed, future prospects in the international market, SWOT assessment is presented. Its potential advantages, weaknesses, opportunities and threats are identified in order to establish a place in the international market of blueberries produced in Georgia. The above mentioned research will help the stakeholders interested in these issues to thoroughly analyze the opportunities for the production and development of blueberries as one of the most promising agricultural crops in Georgia in the future. Based on the analysis, the relevant conclusions are presented.
• Shengelia Z. (1983). samkurnalo mtsenareta kultura sakartveloshi. [Culture of Medicinal Plants in Georgia, Tbilisi.] in Georgian. • Dateshidze L. (2000). saqartveloshi samedicino mcenareta carmoebis infrastruqturis ganvitarebis sakitxebi. evraziis fondis granti, USAID-is resursebi. [Issues of Development of Medicinal Plants Production Infrastructure in Georgia. “mecniereba”, Eurasia Foundation Grant, USAID Resources. Support: ACDI - VOCA (USAID resources) together with GEPA, BESO (British Executive Service Overseas) - TACIS program (United Kingdom), Tbilisi]. in Georgian. • Chavleishvili M. (2012). mocvis msoplio carmoeba da misi ganvitarebis perspeqtivebi saqartveloshi. [World Production of Blueberries and its Development Prospects in Georgia, „Priorities for Sustainable Development of Agriculture“ International Scientific-Practical Conference, Proceedings, TSU]. in Georgian. • Data are processed based on the information of the Food and Agriculture Organization of the United Nations (FAO), (2019). http://www.fao.org/faostat/en/#data/ QC / last view on August 3, 2021 /. in Georgian. • 2020–2021 Blueberry Yearbook Reveals Southern Hemisphere Export Data, June 10, 2021. https://www.producereport.com/article/2020-2021-blueberry-yearbook-reveals- southern-hemisphere-export-data. • sakartvelos plora. [Flora of Georgia. Volume I -XI. Tb., 1971 - 1987.] in Georgian. • motsvis tsarmoebis agroteknologia. [Agrotechnology of Blueberry Production, (2020), USAID REAP, Horticulture.] in Georgian. https://agrokavkaz.ge/dargebi/mebageoba/ motsvis-tsarmoebis-agroteqnologia.html / Last view on August 7, 2021 /. • Richard D., Boboqashvili Z. (2007). lurji mocvi – akhali perspeqtiuli kenkrovani kultura. (2021). [Blueberries - A New Promising Berry Crop, Journal Agroinfo, Tbilisi]. in Georgian. • lurji mocvi – dargva, mulchireba, mosheneba, biznesi, mebageoba (2021). [Blueberry - Planting, Mulching, Cultivation, Business, Gardening, Practical Guide, (2021)]. in Georgian. • https://agrokavkaz.ge/dargebi/mebageoba/lurji-motsvi-dargva-mulchireba- mosheneba-biznesi.html/ Last Vision August 6, 2021 /. in Georgian. • proeqti „danerge momavali“, soplis meurneobis ganvitarebis saagento, kenkrovani kulturebis dafinansebis qveproeqti [Project „Introduce Future“, Agricultural Development Agency, Berries Crop Financing Subproject]. in Georgian. • https://rda.gov.ge/projects/read/plant_future/71:child • „Georgianblue“ lurji mocvis pirveli qartuli brendi msoplio bazarze [“Georgianblue“, the First Georgian Blueberry Brand on the World Market] in Georgian. • https://business-partner.ge/soflis-meurneoba/georgianblue-lurji-motsvis-pirveli- kartuli-brendi-msoflio-bazarze / Last view on August 14, 2021 /.
Keywords: Blueberry world market, blueberry production, blueberry export import, blueberry price